The Effect of Tauroursodeoxycholic Acid (TUDCA) Treatment on Pregnancy Outcomes and Vascular Function in a Rat Model of Advanced Maternal Age - Mazhar Pasha; Raven Kirschenman; Amy Wooldridge; Floor Spaans; Christy-Lynn M. Cooke; Sandra T. Davidge (MDPI AG, 2022)
Advanced maternal age (≥35 years) increases the risk of vascular complications in pregnancy that can result in fetal growth restriction and preeclampsia. Endoplasmic reticulum (ER) stress has been linked to adverse pregnancy outcomes in these complicated pregnancies. However, the role of ER stress in advanced maternal age is not known. We hypothesize that increased ER stress contributes to altered vascular function and poor pregnancy outcomes, and that treatment with the ER-stress inhibitor TUDCA will improve pregnancy outcomes. First, young and aged non-pregnant/pregnant rats were used to assess ER stress markers in mesenteric arteries; mesenteric artery phospho-eIF2α and CHOP expression were increased in aged dams compared to young dams. In a second study, young and aged control and TUDCA-treated dams were studied on gestational day (GD) 20 (term = 22 days). TUDCA treatment was provided via the drinking water throughout pregnancy (GD0-GD20; calculated dose of 150 mg/kg/day TUDCA). ER stress markers were quantified in mesenteric arteries, blood pressure was measured, pregnancy outcomes were recorded, mesenteric and main uterine arteries were isolated and vascular function was assessed by wire myography. Aged dams had increased phospho-eIF2α and CHOP expression, reduced fetal weight, reduced litter size, and impaired uterine artery relaxation. In the aged dams, TUDCA treatment reduced phospho-eIF2α and CHOP expression, reduced blood pressure, improved fetal body weight, and tended to improve uterine artery function compared to control-treated aged dams. In conclusion, our data illustrate the role of ER stress, as well as TUDCA as a potential therapeutic that may benefit pregnancy outcomes in advanced maternal age.